The Cannero Castle (Italy): Development of Radiocarbon Dating Methodologies in the Framework of the Layered Double Hydroxide Mortars. Issue 3 (13th June 2020) - Ricci, Giulia; Secco, Michele; Marzaioli, Fabio; Terrasi, Filippo; Passariello, Isabella; Addis, Anna; Lampugnani, Paolo; Artioli, Gilberto
ABSTRACT: The mortar samples of the Castle of Cannero (Lake Maggiore, Italy) have been characterized and radiocarbon ( 14 C) dated. The presence of LDH phases was identified. The hydraulic reaction was evaluated by a multi-analytical approach. Careful extraction, preparation and purification of the binder fraction have been performed. Contaminations due to LDH phases have been removed allowing reliable absolute dating of the structures. Non-hydraulic lime-based mortars represent only part of the binding materials found in archaeological and historical structures, and a new challenge is the application of 14 C dating techniques on mortars that feature hydraulic reactions. This research work aims at 14 C dating a series of Mg-rich hydraulic mortars from the Castle of Cannero (Lake Maggiore, Italy), from which both charcoals and mortar samples were collected. A multi-analytical approach employing X-ray powder diffraction (XRPD), optical microscopy (OM), and scanning electron microscopy/energy-dispersive microanalysis (SEM-EDS) was adopted in order to carefully characterize the samples. A wet gravimetric separation for the extraction of the fine fraction mainly composed by the mortar binder was carried out and the binder fraction was characterized by XRPD in order to investigate the presence of contaminants. The binding fractions are characterized by the widespread occurrence of hydrotalcite-type minerals, considered contaminants in 14 C dating of mortars because of their capability to exchange carbonate anions even after the hardening process. A further purification treatment by thermal decomposition was performed before 14 C dating by AMS. The obtained dates were consistent with archaeological expectations, confirming the potential of the developed purification methodology for hydraulic mortars dating.